Inclusive financial reform, degree of openness to the outside world, and regional international tourism development: Evidence from a quasi-natural experiment - Fan, Di; Ab Razak, Nazrul Hisyam; Soh, Wei Ni (Elsevier, 2025)
This study selects data from Chinese prefecture-level cities between 2007 and 2023 as the research sample. Based on the quasi-natural experiment of inclusive finance reform experimental zones, it deeply explores the relationship between inclusive finance reform, the degree of openness, and the development of international tourism. The findings reveal a significant positive correlation between inclusive finance reform and the level of international tourism development. Additionally, the impact of inclusive finance reform varies between high-income and low-income regions. The degree of openness also plays a significant moderating role in the relationship between inclusive finance reform and international tourism development.